Using Calls To Action As An Inbound Marketing Conversion Practice - Meslem, Hanane; Abbaci, Ayoub (جامعة الوادي - University of Eloued, 2023)
The development of the new inbound marketing approach focusing on the user led to the emergence of several practices aiming at converting visitors into leads. The objective of our study is to examine the role of calls to action in guiding conversion intent among Algerian Internet users. Our sample consists of 216 respondents generated through a quantitative survey via an online questionnaire. The findings of this research show that overall, calls to action constitute a significant conversion opportunity as long as the content and the counterparty have been clearly identified and assigned an importance by the users. However, conversion may go beyond the traditionally known design criteria, additional factors may take place and drive the conversion action
مقال
Keywords: Inbound marketing ; Call to action ; Conversion